ANALISI YURIDIS KEDUDUKAN KREDITOR SEPARATIS TERKAIT UPAH PEKERJA DARI DEBITOR PAILIT (STUDI KASUS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 67/PUU-XI/2013) - RIYANDA KIRANSYAH (PREMISE LAW JURNAL, 2017)
Abstract Based on Article 55, paragraph (1) of Law No. 37/2004 on Bankruptcy and Postponement of Paying off Debt, secured creditor can execute his right as if there were no bankruptcy. This provision gives him specific position to get the paying off his receivable earlier than the other creditors. However, there are also other creditors who can get their receivables as workers’ wages earlier as it is stipulated in Article 95, paragraph (4) of Law No. 13/2003 on Manpower which states that when a company is filed bankrupt or liquidated according the prevailing regulation, workers’ wages and other rights as the debt should be paid early. In this case, there is a contradiction in norms between the two articles and which creditor that should be prioritized to get his payment. Concerning Article 9 above, Pertamina workers submit judicial review to the Constitutional Court which hands down the Ruling No. 67/PUU-XI/2013. The result of the research shows that by the issuance of the Supreme Court’s Ruling No. 67/PUU-XI/2013, the position of secured creditor which used to be higher than that of workers’ wages is now under the workers’ wages. In getting their paying of their receivables as wages, now workers have their right to precede secured creditors. Keyword : Secured Creditor, Workers’ Wages